HUMAN NEUTROPHIL CHEMOTACTIC RESPONSE TO ACTINOMYCES ISRAEL II: RESPONS KHEMOTAKSIS NETROFIL TERHADAP ACTINOMYCES ISRAEL II - Tetiana Haniastuti (TALENTA, 2012)
Apical periodontitis is an inflammation and destruction of periradicular tissues caused by bacteria of endodontic origin.Actinomyces israel II has been consistently isolated from the periapical tissue of teeth which did not respond to properconventional endodontic treatment. Inflammatory processes are characterized by the dynamic influx of neutrophils whichis initiated by chemical signals including chemotactic factors. The purpose of this preliminary study was to evaluatechemotactic response of neutrophil to A. israel II. Chemotactic activity was performed in vitro with blind well chambers.Hanks balanced salt solution (HBSS) containing 104, 106, and108 A. israel II, 10-8 M N-formyl-L-methionyl-L-leucyl-Lphenylalanine (fMLP), or HBSS were placed in the lower wells of the chamber and covered with 5 Âµm polycarbonatemembrane filters. Neutrophils suspension (2X105 cells) was placed in the upper compartment and incubated for 60 minsat 37Â°C in a humidified atmosphere with 5% CO2. The filters were then removed and stained with Giemsa. Statisticalanalysis used ANOVA test. The result showed that there were significant differences of the number of neutrophils amonggroups (p<0.05), indicating that A. israel II induced neutrophils chemotaxis. The number of neutrophils migrations inresponse to 106, and108 A. israel II were significantly greater compared to 10-8 M fMLP (p<0.05). In conclusion, A. israelII directly induced chemotactic response of neutrophil, therefore, A. israel II may contribute to the pathogenesis of apicalperiodontitis through modulation of the host innate immune response